Study of Soil Infiltration Rate in Some Type of Lands at Desa Sempajaya Kecamatan Berastagi Kabupaten Karo - Rika Isnaini; Sumono Sumono; Ainun Rohana (Universitas Sumatera Utara, 2013)
Infiltration is a very important component in soil conservation. Because as it coralation with rain intensity, run off, and erosion. The aim of this research was to know the infiltration rate in some type of lands i.e chili field, coffee field, and bush at Sempajaya Kecamatan Berastagi Kabupaten Karo using Philips equation model. Parameters observed were moisture content, soil texture, bulk density, particle density, porosity, organic matter and cumulative infiltration was used. Double ring infiltrometer that pressed into the soil, and filled with water was used. The decreased of water was observed with interval of 0, 5, 10, 20, 30, 45, 60, 120, 180, 240 minutes. The results showed that the highest infiltration rate was found in bush, followed by chili field, and the smallest was found in coffee field. The biggest influence on the infiltration rate was organic matter. Key words: Infiltration rate, chili field, coffee field, bush, Sempajaya